Characterization of neuropsychiatric symptoms in a group of individuals with manifest or pre-motor Huntington's disease in Medellín, Colombia. (1st June 2022) - Vasquez, D.; Agudelo, M.; Gomez, C.; Aguillon, D.; Quintero, J.; Rassi, S.; Zuluaga, M.; Pineda, D.; Buritica, O.; Lopera, F.
Abstract : Introduction: Huntington's disease (HD) is a rare (1-9/100 000), inherited disease characterized by an elongated CAG repeat on chromosome 4p, leading to a degeneration of neurons. Also, psychiatric symptoms are very common in the early stage and may appear before motor symptoms. Objectives: To characterize neuropsychiatric symptoms in a group of individuals with manifest or pre-motor Huntington's disease in Medellín, Colombia. Methods: Data obtained from clinical records of individuals with HD (motor-manifest or pre-motor with triplets count) evaluated for ENROLL-HD project in the Group of Neuroscience of Antioquia. We explored variables related to substances abuse, neuropsychiatric symptoms, the respective age of onset, sex, and triplet count when available. Results: Twenty-six (53%) were women, 8% had a familiar history of psychotic illness in a first-degree relative and 88% presented motor symptoms. Also, 59% had a history of depression, 53% irritability, 57% aggressiveness, 34% apathy, 29% perseverative/obsessive behavior, 14% psychosis, and 30% mild cognitive impairment. Ten individuals (20%) had motor without neuropsychiatric symptoms. Also, thirty-seven individuals (76%) presented motor and neuropsychiatric symptoms; of these, 41% had neuropsychiatric symptoms before motor symptoms. No psychiatric symptoms were associated with the use of alcohol, cigarettes, or drugs of abuse. Conclusions: Neuropsychiatric symptoms are highly prevalent among individuals with HD and studies oriented to create relevant knowledge for the development of advice oriented to people with this disease are necessary. Disclosure: No significant relationships.